Multimodal cadmium resistance and its regulatory networking in Pseudomonas aeruginosa strain CD3 - Soumya Chatterjee; Partha Barman; Chandan Barman; Sukanta Majumdar; Ranadhir Chakraborty (Scientific Reports)
Abstract Cadmium, a toxic heavy metal, poses significant global concern. A strain of the genus Pseudomonas, CD3, demonstrating significant cadmium resistance (up to 3 mM CdCl2.H2O) was identified from a pool of 26 cadmium-resistant bacteria isolated from cadmium-contaminated soil samples from Malda, India. The minimum inhibitory concentrations (MICs) for cadmium and other heavy metals/metalloids were determined with clarity using a modified chemically-defined medium inoculated with variable inoculum density. Formation of biofilm enabled CD3 cells to resist up to 0.75 mM CdCl2.H2O. Survival and growth of CD3 cells in presence of > 1 mM CdCl2.H2O was dependent on efflux mechanism. Efflux mechanism in CD3 was confirmed by atomic absorption spectroscopy. Resistance to cadmium was inducible when grown in presence of ≥ 1.0 mM CdCl2.H2O. Minimum concentration of cadmium or zinc or cobalt salts required for induction of cadmium resistance was determined. Whole-genome-based phylogenetic tools identified CD3 as the closest relative to Pseudomonas aeruginosa DSM50071T. Bioinformatic analyses revealed a complex network of regulations, with BfmR playing a crucial role in the functions of CzcR and CzcS, essential for biofilm formation and receptor signalling pathways. Comparative genomics and mutation landscape analyses of cadmium-resistance genes in P. aeruginosa strains revealed dynamism in evolution of cadmium resistance.